A Study on the Waste Disposal Practices and Its Impact in Alappad Panchayat, Kerala - Subramoniam, Vivek; Suresh, Veena (International Journal of Social Sciences and Management, 2015)
Waste is always an important problem in this era, where people are not aware of the waste they produce in their household or institutions. Waste is directly linked to human development, both technological and social. The compositions of different wastes have varied over time and location, with industrial development and innovation being directly linked to waste materials. Examples of this include plastics and nuclear technology. Some waste components have economic value and can be recycled once correctly recovered. Waste is sometimes a subjective concept, because items that some people discard may have value to others. With increase in the global population and the rising demand for food and other essentials, there has been a rise in the amount of waste being generated daily by each household. Alappad is a coastal village in the Kollam District of the Indian state Kerala. It is situated on a narrow strip of land sandwiched between the Arabian Sea a few species of ham and the TS Canal - the village is approximately 16 km long and its narrowest point is as thin as 33 meters. So the household people and petty shop people are not at all aware of the waste disposal they have been practising for a long time. The practise they make every day become a habit which affect their habitat with waste problems. Collective effort from a village can be initiated for a waste management process. Making a prompt step will be intended for effective waste management or disposal solution leads to a proper waste management process. Community level intervention should have to be done for a effective outcome. The purpose of this study is to analyse the waste disposal at the community located in the Alappad Panchayat in Kollam district of Kerala. The scope of this study within the community is assessed based upon following a three-fold approach. Firstly the awareness of community on the waste production within this community is examined. Secondly, the disposal method or model is evaluated and compared within this community. Thirdly, the Waste Disposal of the members of the community is gauged. The study was conducted upon a thin section of the society belonging to a specific ethnographic framework with the focus upon twenty participants. Data was collected via interviews and through the administration of an observation checklist. The results of this study can be extrapolated to project the overall effect Waste Management or Waste disposal in coastal villages throughout the entire nation of India. DOI: http://dx.doi.org/10.3126/ijssm.v2i2.12289 Int. J. Soc. Sci. Manage. Vol-2, issue-2: 97-101